Acute:chronic workload ratio and training monotony variations over the season in youth soccer players: A systematic review - Rico-González, M.; Oliveira, R.; González Fernández, F. T.; Clemente, F. M. (International Journal of Sports Science & Coaching, 2023)
Since acute:chronic workload ratio and training monotony have been criticized as injury risk predictors, the use of intensity measures should be more oriented to understand the variations of intensity across the season. The aim of this systematic review is to summarize the main evidence about the acute:chronic workload ratio and training monotony variations over the season in youth soccer players. The search was made in PubMed, SPORTDiscus, and FECYT (Web of Sciences, CCC, DIIDW, KJD, MEDLINE, RSCI, and SCIELO) according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. From the 225 studies initially identified, 13 were fully reviewed, and their outcome measures were extracted and analyzed. Nine analyzed acute:chronic workload ratio, seven analyzed monotony, and four studies analyzed both acute:chronic workload ratio and monotony. Overall, the range values for acute:chronic workload ratio were 0.58-17.5 AU, while for monotony were 0.83-23.0 AU which showed a higher variability. Few studies showed an association between higher values of acute:chronic workload ratio and/monotony with injury risk or to prevent health problems. These measures could be used to understand the variations of the data through the in-season periods. However, caution is necessary due to the scarce studies performed in young soccer players.